Encyclopedia of global religion - Juergensmeyer, Mark; Roof, Wade Clark (Sage, 2012)
"The multi-volume Encyclopedia of Global Religion provides a comprehensive overview of the globalization of religious culture and society around the world in both its historical and contemporary aspects. The encyclopedia includes topics related to the diaspora of cultures and dispersions of peoples; the transitional aspects of religious ideas and practices; the cultural diversity of religious traditions; and the responses of religion-both negative and positive-to multicultural society. The volumes include essays on the contemporary religious society of every country in the world. The contributors to the encyclopedia are leading authorities on these topics from around the world."-Provided by publisher